Perceived Levels of School Climate, President Leadership, Professional Development, and University Teacher Leadership Competency in Public Universities in China - Ji, XIA; Mohamad, Mua'azam (Journal of Cultural Analysis and Social Change, 2025)
This study examines the perceived levels of school climate, president leadership, professional development, and university teacher leadership competency in public universities in Shapingba District, Chongqing, China. Responding to increasing policy emphasis on leadership capacity building in Chinese higher education, the study establishes a descriptive baseline of key institutional and leadership-related constructs. A quantitative cross-sectional survey was administered to 375 university teachers, and descriptive statistical analyses were conducted to assess central tendencies and variability across constructs. The findings indicate that all four constructs were perceived at moderate to moderately positive levels, suggesting that supportive institutional conditions are present but not yet fully developed into transformative leadership and learning systems. By providing empirical clarity on the current state of leadership-related conditions, this study contributes to the limited descriptive literature on university teacher leadership in China and informs institutional planning, leadership development, and professional learning strategies in higher education.